Unequal Opportunities, Social Groups, and Redistribution: Evidence from the General Population - Rene Schwaiger; Jürgen Huber; Michael Kirchler; Daniel Kleinlercher; Utz Weitzel (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
In this paper we investigate the generalizability of the role of unequal opportunities and social group membership in redistributive preferences for the general population. We present results from a large-scale online experiment with more than 4,000 participants. The experiment consists of a real-effort task and a subsequent dictator game with native Germans and immigrants to Germany. We find that dictator transfers to the own group by native Germans and immigrants are higher under unequal opportunities than under equal opportunities. While we confirm the main findings reported in previous literature regarding the role of inequality of opportunity in redistribution for native Germans and immigrants, we find distinctively different patterns between both groups concerning the influence of social group membership on redistribution. In particular, immigrant dictators transfer more to in-group than to out-group receivers under unequal opportunities and do not compensate unequal opportunities for out-group members, which we do not find among native dictators. We conclude that in order to increase the understanding of patterns reported in the literature, it is crucial to also investigate the external validity of findings with general population samples and to explicitly cover participants such as immigrants who represent important parts of our society.
Keywords: C91; G11; G41; 330; online experiment; redistribution; fairness; migration